Answer:
a
Step-by-step explanation:
inverse ----> y = x
x = 2y - 7
2y = x + 7
y = (x+7)/2
Answer:
280
Step-by-step explanation:
you multiply 10 to 33 and that is p
Answer:
Answer image is attached.
Step-by-step explanation:
Given rational expressions:
![1.\ \dfrac{x^2+x+4}{x-2}\\2.\ \dfrac{x^2-x+4}{x-2}\\3.\ \dfrac{x^2-4x+10}{x-2}\\4.\ \dfrac{x^2-5x+16}{x-2}](https://tex.z-dn.net/?f=1.%5C%20%5Cdfrac%7Bx%5E2%2Bx%2B4%7D%7Bx-2%7D%5C%5C2.%5C%20%5Cdfrac%7Bx%5E2-x%2B4%7D%7Bx-2%7D%5C%5C3.%5C%20%5Cdfrac%7Bx%5E2-4x%2B10%7D%7Bx-2%7D%5C%5C4.%5C%20%5Cdfrac%7Bx%5E2-5x%2B16%7D%7Bx-2%7D)
And the rewritten forms:
![(x-2)+\dfrac{6}{x-2}\\(x+3)+\dfrac{10}{x-2}\\(x+1)+\dfrac{6}{x-2}\\(x-3)+\dfrac{10}{x-2}](https://tex.z-dn.net/?f=%28x-2%29%2B%5Cdfrac%7B6%7D%7Bx-2%7D%5C%5C%28x%2B3%29%2B%5Cdfrac%7B10%7D%7Bx-2%7D%5C%5C%28x%2B1%29%2B%5Cdfrac%7B6%7D%7Bx-2%7D%5C%5C%28x-3%29%2B%5Cdfrac%7B10%7D%7Bx-2%7D)
We have to match the rewritten terms with the given expressions.
Let us consider the rewritten terms and let us solve them one by one by taking LCM.
![(x-2)+\dfrac{6}{x-2}\\\Rightarrow \dfrac{(x-2)^{2}+6 }{x-2}\\\Rightarrow \dfrac{x^2-4x+4+6 }{x-2}\\\Rightarrow \dfrac{x^2-4x+10}{x-2}](https://tex.z-dn.net/?f=%28x-2%29%2B%5Cdfrac%7B6%7D%7Bx-2%7D%5C%5C%5CRightarrow%20%5Cdfrac%7B%28x-2%29%5E%7B2%7D%2B6%20%7D%7Bx-2%7D%5C%5C%5CRightarrow%20%5Cdfrac%7Bx%5E2-4x%2B4%2B6%20%7D%7Bx-2%7D%5C%5C%5CRightarrow%20%5Cdfrac%7Bx%5E2-4x%2B10%7D%7Bx-2%7D)
So, correct option is 3.
![(x+3)+\dfrac{10}{x-2}\\\Rightarrow \dfrac{(x+3)(x-2)+10}{x-2}\\\Rightarrow \dfrac{(x^2+3x-2x-6)+10}{x-2}\\\Rightarrow \dfrac{x^2+x+4}{x-2}](https://tex.z-dn.net/?f=%28x%2B3%29%2B%5Cdfrac%7B10%7D%7Bx-2%7D%5C%5C%5CRightarrow%20%5Cdfrac%7B%28x%2B3%29%28x-2%29%2B10%7D%7Bx-2%7D%5C%5C%5CRightarrow%20%5Cdfrac%7B%28x%5E2%2B3x-2x-6%29%2B10%7D%7Bx-2%7D%5C%5C%5CRightarrow%20%5Cdfrac%7Bx%5E2%2Bx%2B4%7D%7Bx-2%7D)
So, correct option is 1.
![(x+1)+\dfrac{6}{x-2}\\\Rightarrow \dfrac{(x+1)(x-2)+6}{x-2}\\\Rightarrow \dfrac{x^{2} +x-2x-2+6}{x-2}\\\Rightarrow \dfrac{x^{2} -x+4}{x-2}](https://tex.z-dn.net/?f=%28x%2B1%29%2B%5Cdfrac%7B6%7D%7Bx-2%7D%5C%5C%5CRightarrow%20%5Cdfrac%7B%28x%2B1%29%28x-2%29%2B6%7D%7Bx-2%7D%5C%5C%5CRightarrow%20%5Cdfrac%7Bx%5E%7B2%7D%20%2Bx-2x-2%2B6%7D%7Bx-2%7D%5C%5C%5CRightarrow%20%5Cdfrac%7Bx%5E%7B2%7D%20-x%2B4%7D%7Bx-2%7D)
So, correct option is 2.
![(x-3)+\dfrac{10}{x-2}\\\Rightarrow \dfrac{(x-3)(x-2)+10}{x-2}\\\Rightarrow \dfrac{x^2-3x-2x+6+10}{x-2}\\\Rightarrow \dfrac{x^2-5x+16}{x-2}](https://tex.z-dn.net/?f=%28x-3%29%2B%5Cdfrac%7B10%7D%7Bx-2%7D%5C%5C%5CRightarrow%20%5Cdfrac%7B%28x-3%29%28x-2%29%2B10%7D%7Bx-2%7D%5C%5C%5CRightarrow%20%5Cdfrac%7Bx%5E2-3x-2x%2B6%2B10%7D%7Bx-2%7D%5C%5C%5CRightarrow%20%5Cdfrac%7Bx%5E2-5x%2B16%7D%7Bx-2%7D)
So, correct option is 4.
The answer is also attached in the answer area.
X+y+z≥627
x=222
y=194
222+194+z≥627
if we solved for z then
z≥221